Pengembangan E-Module Sistem Ekskresi Berbasis Model OIDDE untuk Peserta Didik MTsN Kota Batu - Indriani, Vivi; Hudha, Atok Miftachul; Hindun, Iin (Journal of Natural Sciences, 2026)
Biology learning on the human excretory system topic often encounters challenges due to the abstract and complex nature of the material, thus requiring interactive digital teaching materials that can enhance students’ engagement in the learning process. This study aimed to develop an excretory system e-module based on the OIDDE learning model (Orientation, Identify, Discussion, Decision, and Engage in Behavior) and to determine its validity and practicality. This research employed a Research and Development (RD) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The product was validated by subject matter, language, and media experts and was limitedly tested with one biology teacher and 30 eighth-grade students at MTsN Kota Batu. Data were collected using validation sheets and response questionnaires based on a four-point Likert scale and were analyzed descriptively using percentage calculations. The results showed validity levels of 85% from subject matter experts (valid), 90% from language experts (very valid), and 95% from media experts (very valid). The practicality test results indicated percentages of 95% from the teacher and 90% from students, both categorized as very practical. Therefore, the OIDDE-based e-module is considered valid and practical and has the potential to support more active and meaningful biology learning at the junior secondary school level.